The Effect of Labor, Capital and Land Area on Rice Farming Production in Bajeng District, Gowa Regency - Asriadi, Andi Amran; Firmansyah, Firmansyah; Husain, Nailah (Jurnal MeA (Media Agribisnis), 2024)
Rice farming is an agricultural activity with plant raw materials that are used for food, which is usually synonymous with smallholder agriculture. Then farmers harvest rice in part to get income. This research was conducted on rice farming in Bajeng District, Gowa Regency. The objectives of this study were 1) to determine the effect of labor, capital and land simultaneously on rice production in Bajeng District, Gowa Regency, 2). to determine the partial effect of labor, capital and land on rice production in Bajeng District, Gowa Regency. The sampling method used in this research is Slovin, the sampling technique used in this research is simple random sampling. The total population of 200 people is taken 15-20% accuracy and if the population is less than 40 farmers. This study uses descriptive and quantitative analysis. The results of the analysis showed the regression coefficient value of each independent variable of rice farming in Bajeng District, Gowa Regency, namely. The variables of labor (TK) and land area (LL) have a positive effect on rice income, while capital (M) has a negative effect on the income of rice farmers. The results of hypothesis testing show that labor and land together have a significant effect on the production of paddy rice. Capital variable has no significant effect on paddy production. While the variables of labor, capital and land partially affect rice paddy production, it can be seen from the results of the t test that there is no influence between rice paddy production. Decision making is done by looking at the importance value. In general, testing regression results is based on a 95% confidence level or a significance level of 5% (Î± = 0.05)